2017
DOI: 10.1186/s12906-017-1708-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low back pain patients’ use of, level of knowledge of and perceived benefits of complementary medicine: a cross-sectional study at an academic pain center

Abstract: BackgroundChronic pain patients often use complementary medicine (CM) to alleviate their pain; however, little is known about the use of CM by chronic low back pain (cLBP) patients. We investigated the frequency of use of CM by cLBP patients, the perceived effects of these therapies, patients’ knowledge regarding CM, and patient-physician communication regarding CM.MethodA cross-sectional survey was conducted from November 2014 to February 2015. A questionnaire was distributed by physicians to 238 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
5
16
0
Order By: Relevance
“…In the United States, it is estimated that 62% of adults have used some form of complementary or alternative therapy in the last 12 months [17], although adult use specifically of essential oils or aromatherapy is unknown. A recent Swiss study estimated that 10.7% of patients with chronic low back pain used aromatherapy and rated it a 4.2 out of a 10-point scale for usefulness [18]. Other studies have shown that aromatherapy may have health benefits, including relief from anxiety and depression, improved quality of life, improved sleep, and pain relief for knee osteoarthritis and renal colic [19–25].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, it is estimated that 62% of adults have used some form of complementary or alternative therapy in the last 12 months [17], although adult use specifically of essential oils or aromatherapy is unknown. A recent Swiss study estimated that 10.7% of patients with chronic low back pain used aromatherapy and rated it a 4.2 out of a 10-point scale for usefulness [18]. Other studies have shown that aromatherapy may have health benefits, including relief from anxiety and depression, improved quality of life, improved sleep, and pain relief for knee osteoarthritis and renal colic [19–25].…”
Section: Discussionmentioning
confidence: 99%
“…111 Both techniques are now working on evidenced-based approach with positive characteristics, collaborating with conventional doctors, and receiving patients acceptance in the treatment of diverse pains. [112][113][114] Massage, reiki, shiatsu. Are manual therapies that prevent or correct mechanical derangements in association with muscles and skeleton, with benefits in short and long term, they have grown significantly.…”
Section: Energy-based Therapiesmentioning
confidence: 99%
“…[ 13 14 ] Given these limitations of pharmacological therapies, it is unsurprising that 1 study showed 77.3% of non-specific LBP patients in Switzerland chose to consult a complementary and alternative medicine (CAM) at a local pain center. [15] Furthermore, the American College of Physicians has revised its recommendation guidelines to suggest CAM treatment options for the management of non-specific LBP. [16] …”
Section: Introductionmentioning
confidence: 99%